A Study on the Use of Learning Media and Its Implications for Student Learning Motivation - Titik Rukmawati; Richard Semuel Waremra; Seli Marlina Raja Leba; Oktin Kristina Hutapea; Deasy Natalia Mulalinda (Edumaspul: Jurnal Pendidikan, 2023)
Learning media plays an important role in increasing student motivation in various educational contexts. In addition, the use of varied and interesting learning media can motivate students to be actively involved in the learning process, increase their interest in subjects, and develop cognitive and social skills. This study aims to investigate the relationship between learning media and student learning motivation. By applying quantitative methods, this research was applied to class XI of IPA YPPK Yosudarso High School Merauke, South Papua, with a total of 18 students. Data collection was carried out by questionnaires consisting of four categories of choices, in addition, for sampling techniques, the Convinience Sampling Method was used as a data collection method. As a finding, the level of learning media is at a high level with mean score = 3.60 while student learning motivation is at a very high level namely meanscore = 4.69. The results showed that there was a significant relationship between learning media and student learning motivation. However, although learning media has great potential to increase student learning motivation, other factors such as students' physical and psychological conditions, learning environment, and the role of parents also play a role in influencing student learning motivation. In addition, the role of teachers in integrating learning media with the right teaching methods is also an important factor. Teachers who are able to use learning media effectively can increase the attractiveness and relevance of learning, and provide positive feedback to students. This can increase students' learning satisfaction and encourage their motivation to continue learning and achieve better results.